PENGARUH NET PROFIT MARGIN DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON EQUITY PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dila Dahlia, Eka (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
The aim of this research was to determine how much influence net profit margin and total assetturnover to return equity in LQ 45 companies listed in the Indonesia Stock Exchange. Number ofsample in this research is 37 LQ 45 companies that listed in Indonesia Stock Exchange (BEI). Thisresearch used multiple linier regression method to verify hypothesis in this research. Beforehypothesis testing all variable must be free from multicollinearity, heteroscedasticity,autocorrelation and normally distributed. The result of this research using t test is net profitmargin have significantly effect to return on equity and total asset turnover have significantly effectto return on equity. Using F test is together with net profit margin and total asset trunover hassignificant impact to return on equity.Key word : Profit Margin, Total Asset Turnover and Return on Equity